Social representations elaborated by mothers on the care of the child with congenital heart disease in the hospital - Frota, Marília Ximenes Freitas; Rodrigues, Dafne Paiva; Pinheiro, Joana Angélica Marques; Bastos, Fatima Maria Coelho Bezerra (Seven Editora, 2023)
This article discusses part of the results of a multi-method research of Doctoral Thesis.The study aims to describe the social representations of mothers about the care of their children with congenital heart disease. Descriptive guided by the Theory of Social Representations (SRT), developed in two stages. The first stage had 88 mothers to apply the sociodemographic questionnaire and the Test of Free Association of Words (TALP), which contained as inducing stimuli: heart disease, caring for the child with heart disease and mother-child relationship in the hospital. Eight mothers participated in the second stage for the semi-structured interviews. It was carried out in a reference hospital in the North and Northeast of the country in the treatment of congenital heart disease linked to the Secretary of Health of the State of Ceará. The data collected through TALP were transcribed and processed by the Trideux software, version 5.3. The statements obtained from the interviews were organized based on Bardin's content analysis. The data obtained by both techniques (TALP and interviews) were categorized and substantiated with RRT, emerging the following categories: Social representations of mothers about the moment of diagnosis: apprehension of a new reality; Social representations of mothers about maternal care in the hospital routine and social representations about maternal feelings. The results showed that maternal representations are related to the importance of understanding the child's diagnosis with clear information, that maternal care in the hospital is carried out with feelings of pain, despair, worry, insecurity and difficulties and is overcome through love and faith, which makes it special and that the mother-child relationship is adapting to the new reality in the hospital experience and with the experience of other mothers and health team.  Therefore, apprehending the social representations of these mothers about the care of their children with congenital heart disease in the hospital is a path in search of quality care to the mother-child dyad, in which it is necessary to awaken in these mothers the value they have when caring for their children in the hospital. It is important that the health team understands the maternal social representations to plan interventions that can alleviate the suffering and support them in the care throughout the hospitalization.DOI:https://doi.org/10.56238/globalhealthprespesc-070